Matcha – an ordinary tea or a superfood with remarkable health benefits? A review of human and animal studies - Ziemińska, Julia; Małek, Michał; Wojtaszek, Oktawia; Skowron, Aleksandra; Orzeł, Jakub; Przygoda, Aleksandra; Pelczar, Patrycja (Quality in Sport, 2026)
Introduction: Matcha is a powdered form of green tea, characterized by a high content of bioactive compounds, like catechins, caffeine, theanine and dietary fiber. By its unique cultivation and processing methods, matcha has attracted scientific interest as a functional food with potential health-promoting properties. Aim: The aim of this review was to summarize current knowledge regarding the chemical composition of matcha tea and to evaluate the evidence concerning its effects on cognitive function, cardiometabolic health, inflammation, cancer prevention, and exercise performance. Methodology: A narrative review of the available scientific literature was conducted using peer-reviewed articles, reviews, experimental studies, and clinical trials concerning matcha tea and its major bioactive compounds. The collected studies were analyzed to assess the potential health effects of matcha consumption. Results: The available evidence indicates that matcha may support cognitive function, improve attention, reduce stress and enhance sleep quality. Furthermore, its consumption may improve lipid and glucose metabolism, reduce inflammation and oxidative stress and exert favorable effects on cardiometabolic health. The high concentration of catechins, particularly epigallocatechin-3-gallate, appears to play a central role in its antioxidant and anti-inflammatory activities. The studies also suggest potential anticarcinogenic properties, while recent findings indicate that matcha supplementation may support adaptation to resistance training by reducing fatigue and enhancing muscle strength. Conclusions: Matcha tea represents a promising functional food with potential benefits for cognitive, metabolic, and overall health. However, many of the reported effects are based on animal studies or small human trials. Further large-scale, long-term randomized controlled studies are required to confirm these findings and establish evidence-based recommendations for matcha consumption.